Optimisation of Tensile Strength and Weight Loss via Taguchi and Response Surface Method for Natural Rubber Latex Film Consisting Cassava Peel as a Bio-Based Filler - Mustaffar, Mahiratul Husna; A. Razak, Aliff Hisyam (Journal of Advanced Industrial Technology and Application, 2021)
Disposal latex and synthetic rubber gloves is troublesome such that disposal via incineration and land fill may release poisonous gasses and contaminate soil and water, respectively. As solution to latex and synthetic rubber, biodegradable glove is extensively studied. A bio-based filler is extracted from food waste and blended into natural rubber latex (NRL) as a composite NRL. The effect of biodegradability of composite NRL was studied by varying the loading of bio-based filler in a form of starch dispersion and blended into NRL mixture. Herein some amount of starch can be extracted from cassava peel to be incorporated in NRL for a sustainable and yet biodegradable glove. Previous work on incorporation of cassava-peel filler in NRL has shown a biodegradability without compromising the pristine strength of NRL film at 50% loading starch. In this project, tensile strength and weight loss of prepared composite NRL films were optimised via Taguchi and Response Surface Method (RSM) by means of Design Expert software by varying starch/filler loading, curing temperature and curing drying duration. Due to inadequate data, the optimisation from that previous prepared composite NRL was compared with similar work which utilising NRL and bio-based filler. For Pulungan (2020) study, it can be concluded that the tensile strength of cassava peel starch biodegradable film has the best condition at 50Â°C to 60Â°C at approximately 5.5 hours. Elongation optimum conditions shows contrast value of temperature and time. Meanwhile, for Wendy (2020) study, it shows the best percentage loading of cassava-peel starch is at 20% to achieve high stress and strain at break. The optimised mechanical properties via Taguchi and RSM are rather different and hence validation on mechanical properties at above mentioned conditions need to be performed experimentally.